Drumblek: The Transformation of Percussion Music into Entertainment Arts and Cultural Identity of Salatiga - Rupiyono, Leo Agung; Sunarto, Sunarto; Haryono, Slamet (Journal of Urban Society's Arts, 2025)
The art of drumblek is a percussion music phenomenon typical of Salatiga, Central Java, which was born from local creativity by using musical instruments from used items such as barrels, blek, buckets, and bamboo. This research aims to explore the form, socio-cultural function, and development of drumblek as a performing art. The research method is qualitative with an ethnographic approach, involving field observation and in-depth interviews with the actors and drumblek preservationists. The results show that drumblek has undergone a transformation of the form of performance: from a simple appearance in the style of a traditional drumband to a dynamic carnival performance, complete with costume innovations and variations of instruments. This art continues to maintain the values of togetherness, creativity, and the spirit of mutual cooperation in its community. As a collective entertainment vehicle, drumblek also functions as a medium to strengthen Salatiga’s local cultural identity. Drumblek has become a symbol of pride of the Salatiga community. Thus, drumblek makes an important contribution as an innovative performing art while strengthening the cultural identity of the Salatiga community.